Structures and packing of ferrocenylmethyl methacrylate and ferrocene‐1, 1′‐diylbis(methylene) dimethacrylate. Issue 12 (1st December 2015) - McAdam, C. John; Moratti, Stephen C.; Simpson, Jim
Abstract : Electroactive metallocene polymers are of interest due to the possibility that they offer a muscle‐like response, and in gel systems very large volume changes are possible. The ferrocenyl moiety exhibits physical and electrochemical stability of the neutral and oxidized forms and could be a candidate for use as the redox‐active group in these materials. The title compounds, [Fe(C5 H5 )(C10 H11 O2 )], (I), and [Fe(C10 H11 O2 )2 ], (II), comprise a typical ferrocene core with coplanar and approximately eclipsed cyclopentadienyl (Cp) rings. In (I), there is a single methyl methacrylate substituent, with the other Cp ring unsubstituted. In (II), a methyl methacrylate substituent on each Cp ring completes the structure. In both compounds, there is an s‐ trans geometry of the vinyl and carbonyl components of the methacrylate group. Inversion dimers formed through C—H...O contacts dominate the crystal packing of both molecules. Weak C—H...π(ring) contacts and, in the case of (I), an unusual C—H...π(alkene) contact further stabilize the structures.